2011
DOI: 10.1128/jcm.00979-10
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Infections in Hospitalized Patients in Israel: Epidemiology and Molecular Characterization

Abstract: Adenoviruses can cause a broad spectrum of clinical diseases, most of which are self-limited. However, adenovirus infection can occasionally result in severe or lethal infection. Fifty-five adenovirus serotypes are known today, and they are classified into 7 subgroups (subgroups A to G). Here we examined 282 samples derived from hospitalized patients in Israel (September 2006 to August 2008) who were diagnosed as suffering from adenovirus infections. We used a recently described PCR amplification method and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 28 publications
(30 reference statements)
10
29
0
Order By: Relevance
“…On the other hand, prevalence of HAdV infection in this study was lower than reported from non-Asian countries such as Brazil 7.1% [13], Peru 6.2% [14], Canada 7.73% [15], Columbia 5% [16]. In addition, Michal Mandelboim and colleagues found an infection prevalence of 18.3% in Israel; however, this study included immune deficient patients [17]. The male/female ratio (M/F) of HAdV infected NP samples in our study was 1.16:1,which is lower than previously reported from Israel 1.48:1 [17], Taiwan 1.3:1 [21], and Peru 1.3:1 [14].…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, prevalence of HAdV infection in this study was lower than reported from non-Asian countries such as Brazil 7.1% [13], Peru 6.2% [14], Canada 7.73% [15], Columbia 5% [16]. In addition, Michal Mandelboim and colleagues found an infection prevalence of 18.3% in Israel; however, this study included immune deficient patients [17]. The male/female ratio (M/F) of HAdV infected NP samples in our study was 1.16:1,which is lower than previously reported from Israel 1.48:1 [17], Taiwan 1.3:1 [21], and Peru 1.3:1 [14].…”
Section: Discussionmentioning
confidence: 61%
“…It has been shown earlier that some HAdV types correlated specifically to one or two months throughout the year, or were also found in some years but not in others [43]. Similar genetic epidemiological studies have shown that HAdV types, comprising HAdV-C1, -C2, -B3, -C5, -C6, and -B7 were mainly involved in respiratory tract infections in children living in Argentina, Iceland, Chile, Taiwan, Canada, China, Malaysia, Korea, Israel, Egypt and the USA, respectively [17], [22], [25], [31], [51], [52], [58], [59], [60], [61], [62]. HAdV types -C1, -C2 and -B3 were detected in most of these studies.…”
Section: Discussionmentioning
confidence: 79%
“…Adenovirus types 1, 2, 3, 5, 6, and 7 primarily cause respiratory diseases (26). Among these adenovirus types, HAdV-1, 2, 3, and 7 are the major types associated with acute respiratory illness (27).…”
Section: Discussionmentioning
confidence: 99%